Use of fine ground dune sand as a supplementary cementing material - Alhozaimy, Abdulrahman; Alawad, Omer Abdalla; Jaafar, Mohd Saleh; Al-Negheimish, Abdulaziz; Noorzaei, Jamaloddin (Journal of Civil Engineering and Management, 2014)
The process of Portland cement production is associated with high consumption of energy and resources. Therefore, there is a need to replace the Portland cement with environmental friendly materials. This study was conducted to determine the feasibility of using ground dune sand as cement replacement materials under different curing conditions. Portland cement was replaced by ground dune sand at five levels of replacement (0–40% by weight). The compressive strength of mortar under standard and autoclave curing conditions and the influence of different autoclave temperatures and durations were investigated. The microstructure of selected mixtures was analyzed by XRD and SEM. Results showed that the compressive strength under the standard curing decreased as the level of replacement increased. However, under autoclave curing compressive strength increased as the content of ground dune sand increased. XRD and SEM revealed the absence of calcium hydroxide and the formation of secondary calcium silicate hydrate. The improvement of compressive strength and the absence of calcium hydroxide under autoclave curing indicated that the pozzolanic reaction between silica of dune sand and calcium hydroxide occurred.